The EuroVotePlus experiment. (December 2015) - Laslier, Jean-François; Blais, André; Bol, Damien; Golder, Sona N; Harfst, Philipp; Stephenson, Laura B; Van der Straeten, Karine
This paper reports on an online experiment that took place in several European countries during the three weeks before the 2014 elections for the European Parliament. We created a website where visitors could obtain information about the electoral rules used in different European Member States for this election. Participants were then invited to cast (simulated) ballots for the election according to three voting rules: closed list proportional representation, open list proportional representation with preferential voting, and open list proportional representation with cumulative voting and panachage. Participants were also invited to think about, and experiment with, the idea of electing some members of the European Parliament through pan-European party lists. The data gathered from this study enable researchers to consider the effects of electoral systems on outcomes in individual countries, and also to investigate the potential popularity and effects of Europe-wide European Parliament constituencies.